Diene Incorporation by a Dehydratase Domain Variant in Modular Polyketide Synthases - Hobson, Christian (Nat Chem Biol, 2022)
Modular polyketide synthases (PKSs) are biosynthetic assembly lines that construct structurally diverse natural products with wide-ranging applications in medicine and agriculture. Various mechanisms contribute to structural diversification during PKS-mediated chain assembly, including dehydratase (DH) domain-mediated elimination of water from R and S-configured 3-hydroxy thioesters to introduce E and Z-configured carbon-carbon double bonds, respectively. Here we report the discovery of a novel DH domain variant that catalyses the sequential elimination of two molecules of water from a (3R, 5S)-3, 5-dihydroxy thioester during polyketide chain assembly, introducing a - conjugated E, Z-diene into various modular PKS products. We show that the reaction proceeds via a (2E, 5S)-2-enoyl-5-hydroxy thioester intermediate and involves an additional universally conserved histidine residue that is absent from the active site of most conventional DH domains. These findings expand the diverse range of chemistries mediated by DH-like domains in modular PKSs, highlighting the catalytic versatility of the double hot dog fold.